Progressive web apps with Angular : create responsive, fast and reliable PWAs using Angular - Hajian, Majid (Apress, 2019)
Harness the power of Angular to build fast, high performance progressive web apps that work offline. Learn exactly how to create an Angular Progressive Web App (PWA) from scratch, how you can use different tools to audit and improve it, and leverage Angular CLI or Workbox to turn your app into a PWA. Using browser APIs - including the Credential Management, Payment Request, Geolocation, Web Bluetooth, WebUSB and Generic Sensors APIs - you can unleash the potential of PWAs and build applications that enhance user experience. Angulars game-changing built-in features, including the Angular service worker module, can be leveraged to construct responsive and reliable PWAs that can look and feel just like native mobile apps. You'll learn how to boost your app speed, how to increase user engagement using push notifications, and how to implement offline storage and different caching APIs in Angular. You'll even see how to convert an existing Angular app into a PWA. Whether youre new to building PWAs, or want to learn how to use Angular to improve your app development, Progressive Web Apps with Angular provides the know-how to build and deploy an Angular PWA.- Resumé vydavatel
Keywords: aplikační software; vývoj softwaru; application software; software development; elektronické knihy; příručky; electronic books; handbooks and manuals